2018
DOI: 10.1186/s13148-018-0509-9
|View full text |Cite
|
Sign up to set email alerts
|

Triage of high-risk HPV-positive women in population-based screening by miRNA expression analysis in cervical scrapes; a feasibility study

Abstract: BackgroundPrimary testing for high-risk HPV (hrHPV) is increasingly implemented in cervical cancer screening programs. Many hrHPV-positive women, however, harbor clinically irrelevant infections, demanding additional disease markers to prevent over-referral and over-treatment. Most promising biomarkers reflect molecular events relevant to the disease process that can be measured objectively in small amounts of clinical material, such as miRNAs. We previously identified eight miRNAs with altered expression in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Moreover, we found that differential expression of the identified miRNAs could be confirmed in independent cervical tissue specimens analyzed by a different method . In addition, recent data show increased expression of miR‐15b in HPV‐positive physician‐taken cervical scrapes from women with CIN3 and SCC . Similarly, preliminary miRNA expression data show consistent results for miR‐20a, miR‐93 and miR‐222 in HPV‐positive cervical scrapes (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, we found that differential expression of the identified miRNAs could be confirmed in independent cervical tissue specimens analyzed by a different method . In addition, recent data show increased expression of miR‐15b in HPV‐positive physician‐taken cervical scrapes from women with CIN3 and SCC . Similarly, preliminary miRNA expression data show consistent results for miR‐20a, miR‐93 and miR‐222 in HPV‐positive cervical scrapes (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 65%
“…30 In addition, recent data show increased expression of miR-15b in HPV-positive physician-taken cervical scrapes from women with CIN3 and SCC. 33 Similarly, preliminary miRNA expression data show consistent results for miR-20a, miR-93 and miR-222 in HPV-positive cervical scrapes (Supporting Information Fig. S3).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Analysis of differential microRNA (miRNA) expression for diagnostic and prognostic purposes has gained increasing attention in recent years. Others and we have previously shown that differential miRNA expression between normal and cervical (pre)cancer cannot only be detected in cervical tissue samples but also in cervical exfoliated cells present in cervical scrapes and self-collected cervico-vaginal specimens (selfsamples) [5][6][7][8]. Although the feasibility of miRNA analysis for the triage of hrHPV-positive women has been demonstrated, an optimal miRNA panel for the detection of CIN3 and cervical cancer still remains to be determined [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the expression levels of 10 candidate miRNAs (miR-15b, miR-125b, miR-149, miR-203a, miR-375, miR-20a, miR-31, miR-93, miR-222, let-7b) derived from an earlier feasibility study on cervical scrapes and a study on hrHPV-positive self-samples [6,8] were determined by qRT-PCR in 209 cervical scrapes of hrHPV-positive women (age: 30-83 years) with known underlying histology that have not been tested for miRNAs before. A predictive miRNA classifier for the detection of CIN3 was built, which was applied to the full sample series and subsequently compared to and combined with the DNA methylation marker FAM19A4 [4].…”
Section: Introductionmentioning
confidence: 99%